RevCore thrombectomy device effectively restores venous stent patency by treating iliofemoral caval in-stent restenosis - Taimur Saleem, MD, FACS; Seshadri Raju, MD, FACS (Journal of Vascular Surgery Cases and Innovative Techniques)
Experience with the RevCore mechanical thrombectomy device in a series of 40 patients is described. The device was employed in the treatment of symptomatic in-stent restenosis (ISR) in iliofemoral caval venous stents in these patients. Computed tomography venography was performed preoperatively to differentiate ISR from stent compression in all patients who underwent intervention. All patients were treated in a single session with a mean estimated blood loss of <10 mL with an average operative time of <30 minutes. Alteplase was not used in any patient. All patients were discharged home the same day. Resolution of ≥50% ISR at the end of the procedure on intravascular ultrasound examination was noted in all patients. Symptom resolution was noted in all patients after the use of the RevCore device. No clinical perioperative pulmonary embolism was observed. Only one patient (2.5%) required reintervention during the follow-up period (range, 2-24 months).